(untitled) (TEST Antologia di Diritto Pubblico, 2025)
This paper revisits the longstanding dilemma concerning the objective or subjective function of the administrative process, underscoring how Calamandrei’s relativistic perspective encounters the “absolutes” codified in constitutional principles, which require the jurisdictional function to be oriented toward the protection of individual legal positions. Despite some resistance to fully aligning administrative process with the constitutional model — as suggested by the persistence of the term giustizia amministrativa and by enduring objectivist traits in jurisprudence and scholarly reconstructions — the analysis proposed here calls for emphasizing the bidirectional character of the principle whereby procedural mechanisms serve substantive law. The recognition that individual legal interests in relations with the public administration are protected only when they are recognized by the legal system — according to the legal regulation of public power — makes it possible to capture the specific features of administrative law without subordinating the process either to the protection of the public interest or to a generic interest in objective legality. From this perspective, even the ex officio powers of the administrative judge are aimed at ensuring procedural equality between the parties, and therefore can be fully integrated within a general procedural model that preserves a subjective orientation.